Effective Writing : Improving Scientific, Technical and Business Comunication - Christopher Turk, John Kirkman
Effective communication is vital to science, engineering and business management. This thoroughly updated second edition with a new chapter on the use of computers and word-processors gives clear, practical advice illustrated with real-life examples on how to select, organize and present information in reports, papers and other documents.